HUBUNGAN FAKTOR RISIKO LINGKUNGAN FISIK DAN PERILAKU DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI KELURAHAN MUSTIKAJAYA KOTA BEKASI - Rianasari Rianasari; Suhartono Suhartono; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Dengue fever is a problem that still occurs in many countries that have tropical and sub-tropical climates. The incidence of dengue fever in the city of Bekasi increased in 2014. By 2015 there were 987 cases (IR = 36) with a CFR of 1.1%. Factors affecting the incidence of dengue fever are physical environmental factors and social behavior. The purpose of this study was to analyze the relationship between the physical environment and the behavior of society with the incidence of dengue fever in the Village of Mustikajaya, Bekasi City. The type of research used was observational analytic with cross sectional approach. The population in this study was the entire number of families with a number of 16,086 households spread over the Village of Mustikajaya Bekasi City. The sample in this study was the patients with dengue fever in the year of 2015 and residents who live in the Village of Mustikajaya with the number of 95 samples. Data analysis used was chi square test at the 95% confidence level. The results showed relationships between resting place (p = 0.026), breeding place (p = 0.004), humidity (p = 0.037), the habit of hanging garments (p = 0.031), the practice of PSN (p = 0.012), and knowledge (p = 0.015) with the incidence of dengue fever. There is no relationship between using anti mosquito products (p = 0.066) with the incidence of dengue. It can be concluded that there are relationships between resting place, breeding place, humidity, the habits of hanging clothes, PSN practices, and knowledge with the incidence of dengue fever, while the anti-mosquito products usage habits have no correlation with the incidence of dengue fever in the Village of Mustikajaya Bekasi City.